(untitled) (Swiss Medical Weekly, 2019)
Patient tailored diagnosis and risk stratification in patients with suspected or known coronary artery disease (CAD) are pivotal. At present, cardiac imaging modalities provide the possibility to evaluate the whole ischaemic cascade noninvasively. In asymptomatic patients, the evaluation of the calcium score may be beneficial and also guide the individual preventive strategy. Furthermore, the calcium score provides complimentary information to the information as assessed by functional testing. Coronary computed tomographic angiography (CCTA) is an excellent tool to exclude CAD, having a negative predictive value of 97–99%. Comparably, a normal functional cardiac imaging test (e.g., positron emission tomography (PET); myocardial perfusion SPECT (MPS); cardiac magnetic resonance (CMR); and stress echocardiography) is consistent with a good prognosis and in general an annual cardiac death rate <1%. If a patient has an abnormal imaging test, it is important for risk stratification to evaluate the severity and extent of the abnormality (e.g., the extent and severity of the perfusion defect, or of the wall motion abnormality, which is consistent with the extent of myocardial scar and ischaemia). The patient’s symptoms and the extent of ischaemia, scar and decrease of ejection fraction will guide the strategy, either to an optimal medical therapy or to a further invasive evaluation. If more than 10% of the myocardium are ischaemic, it is very likely that patients will benefit from revascularisation. The current guidelines leave a lot of room as to which test to choose for noninvasive CAD evaluation and risk stratification. The selection of the particular modality is, in part, led by the pretest probability of CAD and local availability, expertise and preference. However, whenever possible, an imaging-based test rather than a “stand-alone” stress ECG should be used. Cardiac imaging has higher sensitivities and specificities to diagnose or exclude CAD compared with stress testing alone. Using a hybrid approach, integrating complimentary information to that given by functional testing (e.g., PET/CT) provides the highest noninvasive diagnostic and prognostic accuracies in CAD evaluation available so far.